Trends and patterns of needs assessments in technical and vocational education: A thematic review - Aziyati Ibrahim; Irdayanti Mat Nashir (International Journal of Evaluation and Research in Education (IJERE), 2022)
It is theoretically acknowledged that needs assessments generally present holistic views in new, quality improvement or extension of projects. Although previous studies demonstrated the significant contributions of approaches and methods, reviews of the literature on needs assessments describing formal and non-formal technical and vocational higher education were excluded. Therefore, a thematic review of patterns and trends concerning on the needs of needs assessments in technical and vocational higher education between 2016 and 2020 was reported. Guided by the systematic review process and thematic analysis by using ATLAS.ti of Scopus, ScienceDirect and EBSCOhost identified 21 related articles. Further review of these articles produced conceptual framework with two main themes: i) “What is?” and “what should be?” to the project; and ii) Needs of needs assessment including input of needs assessment (experts, resources, time, innovative approaches, knowledge and authentic data) and method of needs assessment as preliminary studies tools, needs identification tools, evaluation tools and decision-making tools. Conceptual framework that synthesizes and uses the findings in organizing and categorizing the needs of needs assessment. Significant contributions for practical, multidisciplinary approaches in technical vocational education were presented as implications for prospective research.